Pengembangan Instagram Reels Pembelajaran Pokok Bahasan Persamaan Garis Lurus untuk SMP - Diah Wulandari; I Nyoman Arcana; Krida Singgih Kuncoro (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
Instagram Reel is one of the social media currently popular, but it has not been widely used to create mathematics learning media. This research aims: (1) to develop a learning Instagram Reel for the subject of linear Equations for Junior High School and (2) to find out from the Instagram Reel developed in this study. The research method used is Research and Development (R & R&D) with the ADDIE model, consisting of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 22 students of SMP Negeri 3 Bantul. The result of this research is Instagram Reels learning for the subject of linear Equations for Junior High School, presented through the Instagram account @mathematics_fun. This Instagram reel was declared suitable for use because the average total validation score for aspects was 4.61 (including the very valid category), and the average student response questionnaire score was 3.91 (including the good category). The implication is that teachers are advised to use Instagram Reels as a learning medium. It is recommended that teachers develop Instagram for other materials.